Peningkatan Kunjungan Pariwisata dan Perekonomian Masyarakat Kabupaten Ende melalui Olahraga Bersepeda Tour De Flores - Aschari Senjahari Rawe; Geryani Suryo Moang Kala; Finsensius Mbabho (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2021)
The purpose of this study was to determine the increase in tourist visits and the impact on business actors in improving the community's economy. The research approach used qualitative descriptive methods to determine the increase in regional tourism through the Tour de Flores cycling sporting event. From research, it is known that with the implementation of the Tour de Flores, tourism in Ende Regency has increased from the previous year. The Tour de Flores cycling sport can indirectly achieve its goals, one of which is to improve people's living standards and improve public facilities and facilities. However, it cannot be denied that this increase has not been fully felt by the people of Flores, especially those in Ende Regency. The problems of the government and related institutions must be carried out optimally through increasing human resources, the economy, sports infrastructure and regional tourism innovation prioritizing HR, economic and other aspects. Keywords: Cycling Sports, Tourist Visit, Economy.